Holocaust history and the law: 1985-1995 - V. Ranki (Law Text Culture, 1997)
Perhaps I was among the first dressed in 'zebra' clothes to appear in that place called Trzebinia; I immediately found myself the centre of a dense group of curious people, who interrogated me volubly in Polish. I replied as best I could in German: and in the middle of the group of workers and peasants a bourgeois appeared, with felt hat, glasses and a leather briefcase in his hand - a lawyer.